PENGARUH BI RATE, INFLASI DAN KURS TUKAR TERHADAP PERFORMA LIKUIDITAS PERBANKAN KONVENSIONAL DI MASA PANDEMI COVID-19 - Aditya, Rizqi Dwi; Hariyani, Happy Febrina (Journal of Financial Economics & Investment, 2021)
The liquidity ratio is a metric that measures a bank’s capacity to meet short-term obligations and repay money disbursed when they are due. The goal of this study is to examine the performance of conventional banking liquidity during the covid-19 pandemic, as well as the impact of the BI rate, inflation and exchange rate variables on conventional banking liquidity. Secondary data from public reports on the websites of the Financial Services Authority (OJK), Bank Indonesia (BI), the Central Statistics Agency (BPS), and the Ministry of Trade from the first quarter of 2020 to the first quarter of 2021 was used in this study. Method The analysis used in this study uses panel data regression analysis. The result of this research is that the BI rate variable has a positive and significant effect on liquidity. Inflation and Exchange Rate variables have a negative and significant effect on liquidity.